Improving Breastfeeding Self-Efficacy in Postpartum Mothers Through Hypnobreastfeeding - siti hadijah; Jasmawati ,; Lukman Nulhakim (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Exclusive breast milk is breast milk given to infants from birth for 6 months, without adding from/or replacing other foods and drinks (except medicine, vitamins, and minerals). Breastfeeding Self-Efficacy is the biggest factor that can influence the process of breastfeeding and the success of exclusive breastfeeding. One of the solutions that can help improve breastfeeding self-efficacy is to apply Hypnobreastfeeding. The type of research is quantitative with a pre-experimental research design in the form of a one-group pretest and posttest design, which assesses the effect of Hypnobreastfeeding on Breastfeeding Self-Efficacy on postpartum mothers in the postpartum room of RSUD Kudungga. The sampling technique was taken using consecutive sampling of 23 people. Based on the results of data analysis using the Wilcoxon test, a p value of 0.000 was obtained. Thus p = 0.000 is smaller than the error rate used at the α = 0.05 level. Mothers who breastfeed When they have the belief that their milk is lacking and not enough for the baby, then this belief will be embedded in the subconscious, and the mother will experience what she believes. Hypnobreastfeeding can neutralize these negative recordings for reprogramming by incorporating a positive intention or attitude towards self-confidence to be able to provide breast milk to their babies and believe that milk production is sufficient according to the needs of the baby. It can be concluded that Hypnobreastfeeding does affect the breastfeeding self-efficacy for postpartum mothers in the postpartum room at RSUD Kudungga.